Orange red sodium niobate-calcium titanate stress luminescent material and preparation method thereof
By using a mixture of Na0.985-xCaxPr0.005Nb1-xTixO3 phosphor and an epoxy resin resin, the problem of harmful gas generation and poor luminescence performance of existing stress luminescent materials is solved, and an efficient orange-red stress luminescence effect is achieved.
Patent Information
- Application Number
- CN202411659993.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing stress luminescent materials will produce harmful gases during use, affecting the environment and human health. At the same time, their luminescent performance is poor, making it difficult to meet the needs of high-sensitivity sensors and flexible display technologies.
The sodium niobate-calcium titanate stress luminescent material made of Na0.985-xCaxPr0.005Nb1-xTixO3 as a resin mixture composed of phosphor and an epoxy resin and alicyclic amine was prepared by ball mill mixing and high-temperature solid phase synthesis to form an orange-red light source with good stress luminescent performance.
It has achieved good stress luminescence performance under friction conditions, with an emission wavelength of 580-650nm and an emission center of 611nm, emitting strong orange-red light, which improves the luminescence performance and stability of the material and avoids the generation of harmful gases.
Smart Images

Figure CN119505871A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic luminescent materials, and in particular to an orange-red sodium niobate-calcium titanate stress luminescent material and a preparation method thereof. Background Art
[0002] Photoluminescence refers to the phenomenon that solid materials are illuminated by external light sources to obtain energy, thereby stimulating electrons in the material to achieve luminescence, while stress luminescence refers to the luminescence induced by mechanical stimulation such as friction and compression in solid materials. At present, stress luminescent materials based on fine grinding and compression conditions are widely used to monitor the stress distribution of structural objects, thereby manufacturing highly sensitive sensors, as well as flexible display technology and optical devices.
[0003] The stress luminescent materials currently on the market, such as ZnS:Cu 2+ "Research and Application of Mechanical Properties of Stress Luminescent Films" (Journal of Yancheng Institute of Technology (Natural Science Edition), 2023, 36(04): 64-69), and "K x Na 1-x NbO3:Pr 3+ Photoluminescence and stress luminescence properties of ferroelectrics (Acta Physica Sinica, 2022, 71(16):167801) The stress luminescence materials disclosed in this paper will produce harmful gas sulfur dioxide, which not only poses a threat to the environment and human health, but also affects the service life of the material itself. For example, SrAl2O4:Eu 2+ ,Dy 3+ , there is a defect that it is unstable when in contact with water and undergoes hydrolysis reaction.
[0004] Sodium niobate-based stress luminescent materials can emit visible light or ultraviolet light when subjected to stress, but the luminescent properties of the sodium niobate-based stress luminescent materials currently studied are poor. Summary of the invention
[0005] The invention provides a high-intensity orange-red sodium niobate-calcium titanate stress luminescent material and a preparation method thereof.
[0006] The technical solution provided by the present invention is an orange-red sodium niobate-calcium titanate stress luminescent material, which is composed of a mixture of phosphor and resin. The chemical formula of the phosphor is: Na 0.985-x Ca x Pr 0.005 Nb 1-x Ti x O3, x represents the mole fraction, 0.01≤x≤0.09;
[0007] The resin mixture is composed of epoxy resin and alicyclic amine, and the mass ratio of the two is 3 to 10:1;
[0008] The weight ratio of the phosphor to the resin mixture is 1:1-5.
[0009] The phosphor has an orthorhombic phase structure, Ca 2+ and Pr 3+ Replace Na + The site enters the crystal lattice and has photoluminescence properties. Under the condition of excitation wavelength of 290nm, it emits orange-red light with a wavelength of 580-650nm.
[0010] The stress luminescent material of the present invention has good stress luminescent performance under friction conditions, with an emission wavelength of 580 to 650 nm and an emission center of 611 nm, and emits orange-red light.
[0011] Preferably, 0.03≤x≤0.05.
[0012] More preferably, x=0.03.
[0013] The present invention also provides a method for preparing an orange-red sodium niobate-calcium titanate stress luminescent material, comprising the following steps:
[0014] 1) Na2CO3, Pr6O 11 , CaCO3, TiO2, Nb2O5 as raw materials according to the chemical formula Na 0.985-x Ca x Pr 0.005 Nb 1- x Ti x O3 is used for mixing, anhydrous ethanol is used as a solvent for ball milling, and then the phosphor powder is obtained after being taken out and dried, fired for the first time, ground for the first time, fired for the second time, and ground for the second time;
[0015] 2) mixing the epoxy resin and the alicyclic amine according to a proportion to obtain a resin mixture;
[0016] 3) Pour the formulated amount of phosphor and resin mixture into the mold in sequence, let it stand, dry, and demould to obtain the stress luminescent material.
[0017] In step 1), the ball milling is carried out at a ball milling speed of 100 to 300 r / min for 2 to 12 hours.
[0018] In step 1), the first firing is to increase the temperature to 700-900° C. at a rate of 3-10° C. / min and keep the temperature for 3-9 hours.
[0019] The second firing is carried out at 1050-1200°C for 2-6 hours.
[0020] The first and second grinding times are both 30 to 60 minutes.
[0021] The present invention has the following beneficial effects:
[0022] 1. The present invention adopts ball milling mixing and high-temperature solid phase synthesis method to prepare samples, so that the particle size of the particles is greatly reduced, so that the materials are easier to mix evenly. The high-temperature solid phase synthesis method has the advantages of simple and easy operation, low cost, high product purity, good particle characteristics, etc., and has been widely used in the field of preparation of inorganic materials.
[0023] 2. The present invention adds praseodymium and calcium titanate to sodium niobate, and the obtained composite material has good stress luminescence performance and emits orange-red light with an emission wavelength of 580 to 650 nm. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The XRD test spectra of the phosphors of Examples 1 to 5 and Comparative Example 1 are shown;
[0025] Figure 2 It is the normalized PLE and PL diagram of NPN-0.01CT of Example 1;
[0026] Figure 3 is the photoluminescence spectrum of the phosphor of Example 1;
[0027] Figure 4 The friction stress luminescence spectrum of the stress luminescence material of Example 1;
[0028] Figure 5 is the photoluminescence spectrum of the phosphor of Example 2;
[0029] Figure 6 The friction stress luminescence spectrum of the stress luminescence material of Example 2;
[0030] Figure 7 is the photoluminescence spectrum of the phosphor of Example 3;
[0031] Figure 8 The friction stress luminescence spectrum of the stress luminescence material of Example 3;
[0032] Fig. 9 is the photoluminescence spectrum of the phosphor of Example 4;
[0033] Fig.10 The friction stress luminescence spectrum of the stress luminescence material of Example 4;
[0034] Fig.11 is the photoluminescence spectrum of the phosphor of Example 5;
[0035] Fig.12 The friction stress luminescence spectrum of the stress luminescence material of Example 5;
[0036] Fig.13 is the photoluminescence spectrum of the phosphor of comparative example 1;
[0037] Fig.14 This is the friction stress luminescence spectrum of the stress luminescent material of control example 1. DETAILED DESCRIPTION
[0038] The present invention will be further described below with reference to examples, but the present invention is not limited to these examples.
[0039] Example 1
[0040] 1) Na2CO3, Pr6O 11 , CaCO3, TiO2, Nb2O5 as raw materials according to the chemical formula Na 0.975 Ca 0.01 Pr 0.005 Nb 0.99 Ti 0.01 O3 for batching, namely: 5.1670g Na2CO3, 0.0851g Pr6O 11 , 0.1001gCaCO3, 0.0799gTiO2, and 13.1576gNb2O5 are placed in an agate ball mill, 80ml of anhydrous ethanol is added, and the ball mill is performed at a rotation speed of 100r / min for 2h. After being taken out, it is dried at 80℃; it is sent to an oven for sintering, and the temperature is increased to 700℃ at a rate of 3℃ / min and kept warm for 3h, cooled to room temperature, and ground for 30min; it is sent to the oven for sintering again, kept warm at 1050℃ for 2h, and ground for 30min to obtain the phosphor (abbreviated as NPN-0.01CT).
[0041] 2) Epoxy resin and alicyclic amine are mixed at a mass ratio of 3:1 without generating bubbles to obtain a resin mixture. The phosphor and resin mixture are prepared at a mass ratio of 1:1.
[0042] 3) Apply vaseline on the inner surface of the polytetrafluoroethylene mold, pour the phosphor prepared in step 2) into the bottom of the mold and evenly spread it, then pour the resin mixture prepared in step 2) into the mold, let it stand for 5 minutes in an air atmosphere, then transfer it to an oven, dry it at 60°C for 4 hours, take it out, demold it, and obtain the stress luminescent material.
[0043] In order to prove the phase structure of NPN-0.01CT, XRD test was carried out. The test results are shown in Figure 1 As shown, the diffraction peak of NPN-0.01CT is consistent with the standard peak of sodium niobate, showing a typical perovskite structure. The crystal structure is an orthorhombic perovskite structure. The doping of CaTiO3 does not affect the synthesis of the crystal phase, and no second phase or other impurities are observed.
[0044] In order to prove the photoluminescence performance of NPN-0.01CT, the excitation spectrum and emission spectrum tests were carried out. The test results are shown in Figure 2 As shown. At a wavelength of 611nm, the NPN-0.01CT test obtained an excitation spectrum. Using the optimal excitation wavelength of 290nm, the emission wavelength spectrum of 580-650nm was excited. 3+ of 1 D2→ 3 H4 is obtained by transition, emitting orange-red light.
[0045] The photoluminescence properties of NPN-0.01CT are as follows Figure 3 As shown, under 290 nm light excitation, orange-red emission centered at 611 nm was observed, emitting orange-red light.
[0046] In order to prove the stress luminescence performance of stress luminescence materials, the friction stress luminescence performance test was carried out under the conditions of 15N friction force and ultraviolet light radiation (365nm, 5min). Figure 4 Friction stress test results.
[0047] Example 2
[0048] 1) Na2CO3, Pr6O 11 , CaCO3, TiO2, Nb2O5 as raw materials according to the chemical formula Na 0.955 Ca 0.03 Pr 0.005 Nb 0.97 Ti 0.03 O3 for batching, namely: 5.0610g Na2CO3, 0.0851g Pr6O 11 , 0.3002gCaCO3, 0.2396gTiO2, and 12.8918gNb2O5 are placed in an agate ball mill, 80ml of anhydrous ethanol is added, and the ball mill is performed at a rotation speed of 300r / min for 12h. After being taken out, it is dried at 80℃; it is sent to an oven for sintering, and the temperature is increased to 900℃ at a rate of 10℃ / min and kept for 9h, cooled to room temperature, and ground for 60min; it is sent to the oven again, kept at 1200℃ for 6h, and ground for 60min to obtain the phosphor (abbreviated as NPN-0.03CT).
[0049] 2) Epoxy resin and alicyclic amine are mixed at a weight ratio of 10:1 without generating bubbles to obtain a resin mixture. The phosphor and resin mixture are prepared at a weight ratio of 1:5.
[0050] 3) Apply vaseline on the inner surface of the polytetrafluoroethylene mold, pour the phosphor prepared in step 2) into the bottom of the mold and evenly spread it, then pour the resin mixture prepared in step 2) into the mold, let it stand for 5 minutes in an air atmosphere, then transfer it to an oven, dry it at 60°C for 4 hours, take it out, demold it, and obtain the stress luminescent material.
[0051] In order to prove the phase structure of NPN-0.03CT, XRD test was carried out, such as Figure 1 The diffraction peak is consistent with the standard peak of sodium niobate, and the test result is consistent with Example 1.
[0052] The photoluminescence properties of NPN-0.03CT are as follows Figure 5 As shown, under 290nm light excitation, orange-red emission centered at 611nm was observed, and the light emission position did not change significantly compared with Example 1, emitting orange-red light.
[0053] Figure 6 This is the friction stress luminescence test result of the stress luminescent material. The test conditions are the same as those in Example 1. The friction stress luminescence intensity is 421.77 au.
[0054] Example 3
[0055] 1) Na2CO3, Pr6O 11 , CaCO3, TiO2, Nb2O5 as raw materials according to the chemical formula Na 0.935 Ca 0.05 Pr 0.005 Nb 0.95 Ti 0.05 O3 for batching, namely: 4.9550gNa2CO3, 0.0851gPr6O 11 , 0.5004gCaCO3, 0.3994gTiO2, and 12.6260gNb2O5 are placed in an agate ball mill, 80ml of anhydrous ethanol is added, and the mixture is treated at a rotation speed of 200r / min for 6h. After being taken out, it is dried at 80℃; it is sent to an oven for sintering, and the temperature is increased to 800℃ at a rate of 8℃ / min and kept warm for 5h, cooled to room temperature, and ground for 50min; it is sent to the oven again, kept warm at 1100℃ for 4h, and ground for 45min to obtain the phosphor (abbreviated as NPN-0.05CT).
[0056] 2) Epoxy resin and alicyclic amine are mixed at a weight ratio of 6:1 without generating bubbles to obtain a resin mixture. The phosphor and resin mixture are prepared at a weight ratio of 1:2.5.
[0057] 3) Apply vaseline on the inner surface of the polytetrafluoroethylene mold, pour the phosphor prepared in step 2) into the bottom of the mold and evenly spread it, then pour the resin mixture prepared in step 2) into the mold, let it stand for 5 minutes in an air atmosphere, then transfer it to an oven, dry it at 60°C for 4 hours, take it out, demold it, and obtain the stress luminescent material.
[0058] In order to prove the phase structure of NPN-0.05CT, XRD test was carried out, such as Figure 1 The diffraction peak is consistent with the standard peak of sodium niobate, and the test result is consistent with Example 1.
[0059] The photoluminescence properties of NPN-0.05CT are as follows Figure 7 As shown, under 290nm light excitation, orange-red emission centered at 611nm was observed, and the light emission position did not change significantly compared with Example 1, emitting orange-red light.
[0060] Figure 8 This is the friction stress luminescence test result of the stress luminescent material. The test conditions are the same as in Example 1. The friction stress luminescence intensity is 411.81 au.
[0061] Example 4
[0062] 1) Na2CO3, Pr6O 11 , CaCO3, TiO2, Nb2O5 as raw materials according to the chemical formula Na 0.915 Ca 0.07 Pr 0.005 Nb 0.93 Ti 0.07 O3 for batching, namely: 4.8490gNa2CO3, 0.0851gPr6O 11 , 0.7006gCaCO3, 0.5592gTiO2, and 12.3602gNb2O5 are placed in an agate ball mill, 80ml of anhydrous ethanol is added, and the mixture is ball-milled at a speed of 100r / min for 12h. After being taken out, the mixture is dried at 80℃; the mixture is sent to an oven for sintering, and the temperature is increased to 900℃ at a rate of 3℃ / min and kept at this temperature for 3h, then the mixture is cooled to room temperature and ground for 60min; the mixture is sent to the oven again, kept at 1050℃ for 6h, and ground for 30min to obtain the phosphor (abbreviated as NPN-0.07CT).
[0063] 2) Epoxy resin and alicyclic amine are mixed at a weight ratio of 10:1 without generating bubbles to obtain a resin mixture. The phosphor and resin mixture are prepared at a weight ratio of 1:1.
[0064] 3) Apply vaseline on the inner surface of the polytetrafluoroethylene mold, pour the phosphor prepared in step 2) into the bottom of the mold and evenly spread it, then pour the resin mixture prepared in step 2) into the mold, let it stand for 5 minutes in an air atmosphere, then transfer it to an oven, dry it at 60°C for 4 hours, take it out, demold it, and obtain the stress luminescent material.
[0065] In order to prove the phase structure of NPN-0.07CT, XRD test was carried out, such as Figure 1 The diffraction peak is consistent with the standard peak of sodium niobate, and the test result is consistent with Example 1.
[0066] The photoluminescence properties of NPN-0.07CT are as follows Fig. 9 As shown, under 290nm light excitation, strong red emission centered at 611nm was observed, the light emission position did not change significantly compared with Example 1, and orange-red light was emitted.
[0067] Fig.10 This is the friction stress luminescence test result of the stress luminescent material. The test conditions are the same as those in Example 1.
[0068] Example 5
[0069] 1) Na2CO3, Pr6O 11 , CaCO3, TiO2, Nb2O5 as raw materials according to the chemical formula Na 0.895 Ca 0.09 Pr 0.005 Nb 0.91 Ti 0.09 O3 for batching, namely: 4.7430gNa2CO3, 0.0851gPr6O 11 , 0.9008gCaCO3, 0.7189gTiO2, and 12.0943gNb2O5 are placed in an agate ball mill, 80ml of anhydrous ethanol is added, and the mixture is treated at a rotation speed of 300r / min for 2h. After being taken out, it is dried at 80℃; it is sent to an oven for sintering, and the temperature is increased to 700℃ at a rate of 10℃ / min and kept for 9h, cooled to room temperature, and ground for 30min; it is sent to the oven again, kept at 1200℃ for 2h, and ground for 60min to obtain the phosphor (abbreviated as NPN-0.07CT).
[0070] 2) Epoxy resin and alicyclic amine are mixed at a weight ratio of 3:1 without generating bubbles to obtain a resin mixture. The phosphor and resin mixture are prepared at a weight ratio of 1:5.
[0071] 3) Apply vaseline on the inner surface of the polytetrafluoroethylene mold, pour the phosphor prepared in step 2) into the bottom of the mold and evenly spread it, then pour the resin mixture prepared in step 2) into the mold, let it stand for 5 minutes in an air atmosphere, then transfer it to an oven, dry it at 60°C for 4 hours, take it out, demold it, and obtain the stress luminescent material.
[0072] In order to prove the phase structure of NPN-0.09CT, XRD test was carried out, such as Figure 1 The diffraction peak is consistent with the standard peak of sodium niobate, and the test result is consistent with Example 1.
[0073] The photoluminescence properties of NPN-0.09CT are as follows Fig.11 As shown, under 290nm light excitation, orange-red emission centered at 611nm was observed, and the light emission position did not change significantly compared with Example 1, emitting orange-red light.
[0074] Fig.12 This is the friction stress luminescence test result of the stress luminescent material. The test conditions are the same as those in Example 1.
[0075] Comparative Example 1
[0076] 1) Na2CO3, Pr6O 11 , Nb2O5 as raw materials according to the chemical formula Na 0.985 Pr 0.005 NbO3 is used for batching, namely: 5.2199g Na2CO3, 0.0851g Pr6O 11 13.2905g Nb2O5 was placed in an agate ball mill, 80ml anhydrous ethanol was added, and the mixture was treated at a rotation speed of 100r / min for 2h. After being taken out and dried, it was sent to an oven for sintering, and the temperature was increased to 700℃ at a rate of 3℃ / min and kept for 3h. After being cooled to room temperature, it was ground for 30min. It was sent to the oven again, kept at 1050℃ for 2h, and ground for 30min to obtain the phosphor (NPN).
[0077] 2) Epoxy resin and alicyclic amine are mixed at a weight ratio of 3:1 without generating bubbles to obtain a resin mixture. The phosphor and resin mixture are prepared at a weight ratio of 1:1.
[0078] 3) Apply vaseline on the inner surface of the polytetrafluoroethylene mold, pour the phosphor prepared in step 2) into the bottom of the mold and evenly spread it, then pour the resin mixture prepared in step 2) into the mold, let it stand for 5 minutes in an air atmosphere, then transfer it to an oven, dry it at 60°C for 4 hours, take it out, demold it, and obtain the stress luminescent material.
[0079] In order to prove the phase structure of NPN, XRD test was carried out, such as Figure 1 The diffraction peak is consistent with the standard peak of sodium niobate, and the test result is consistent with Example 1.
[0080] The photoluminescence properties of NPNs are Fig.13 As shown, under 290nm light excitation, orange-red emission centered at 611nm was observed, and the light emission position did not change significantly compared with Example 1, emitting orange-red light.
[0081] Fig.14 This is a friction stress luminescence test result of the stress luminescent material. The test conditions are the same as those in Example 1. The luminescence intensity of the stress luminescent material is relatively poor.
Claims
1. An orange-red sodium niobate-calcium titanate stress luminescent material and a preparation method thereof, characterized in that: The material is composed of a mixture of phosphor and resin, and the chemical formula of the phosphor is: Na 0.985-x Ca x Pr 0.005 Nb 1-x Ti x O3, x represents the mole fraction, 0.01≤x≤0.09; The resin mixture is composed of epoxy resin and alicyclic amine, and the mass ratio of the two is 3 to 10:1; The mass ratio of the fluorescent powder to the resin mixture is 1:1-5.
2. The orange-red sodium niobate-calcium titanate stress luminescent material according to claim 1, characterized in that: 0.03≤x≤0.05。 3. The orange-red sodium niobate-calcium titanate stress luminescent material according to claim 2, characterized in that: x=0.03。 4. The method for preparing the orange-red sodium niobate-calcium titanate stress luminescent material according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) Na2CO3, Pr6O 11 , CaCO3, TiO2, Nb2O5 as raw materials according to the chemical formula Na 0.985-x Ca x Pr 0.005 Nb 1-x Ti x O3 is used for mixing, anhydrous ethanol is used as a solvent for ball milling, and then the phosphor powder is obtained after being taken out and dried, fired for the first time, ground for the first time, fired for the second time, and ground for the second time; 2) mixing the epoxy resin and the alicyclic amine according to a proportion to obtain a resin mixture; 3) Pour the formulated amount of phosphor and resin mixture into the mold in sequence, let it stand, dry, and demould to obtain the stress luminescent material.
5. The method for preparing the orange-red sodium niobate-calcium titanate stress luminescent material according to claim 4, characterized in that: In step 1), the ball milling is carried out at a ball milling speed of 100 to 300 r / min for 2 to 12 hours.
6. The method for preparing the orange-red sodium niobate-calcium titanate stress luminescent material according to claim 4, characterized in that: In step 1), the first firing is to increase the temperature to 700-900° C. at a rate of 3-10° C. / min and keep the temperature for 3-9 hours.
7. The method for preparing the orange-red sodium niobate-calcium titanate stress luminescent material according to claim 4, characterized in that: In step 1), the second firing is carried out at 1050-1200° C. for 2-6 hours.
8. The method for preparing the orange-red sodium niobate-calcium titanate stress luminescent material according to claim 4, characterized in that: In step 1), the first grinding time and the second grinding time are both 30 to 60 minutes.
Citation Information
Patent Citations
Lead-free piezoelectric potassium sodium niobate optoelectronic multifunctional material and preparation method thereof
CN103787658A
Rare earth doped composite red stress luminescent material and preparation method thereof
CN109468132A